Design and Implementation of an Online Learning Behavior Evaluation System Based on Data Mining - Bo Zhang; Jiali Xie (Advances in Multimedia)
In order to study the problem that most of the existing Web-based distance education systems lack the monitoring of the learning process and the evaluation of students’ online learning behavior, a method of designing an online learning behavior evaluation system based on data mining is proposed, and an online learning behavior evaluation system is implemented. The system evaluates students’ online learning and gives formative evaluation results. The evaluation results are more accurate, and the recognition of teachers and students is more than 90%. The application of the system provides methods and means for objective, fair, and reasonable evaluation of students’ online learning and plays a guiding role for students in rationally arranging online learning; 99% of users said that the application of this system has a greater effect on promoting ordinary online learning help. The application of the system promotes students’ online learning to a certain extent, and the “learning behavior-effect” model constructed by the system has guiding significance for students to reasonably arrange online learning.